Interleukin-receptor antagonist and tumour necrosis factor inhibitors for the primary and secondary prevention of atherosclerotic cardiovascular diseases - Martí-Carvajal, Arturo J; Gemmato-Valecillos, Mario A; Monge Martín, Diana; Dayer, Mark; Alegría-Barrero, Eduardo; De Sanctis, Juan Bautista; Parise Vasco, Juan Marcos; Riera Lizardo, Ricardo J; Nicola, Susana; Martí-Amarista, Cristina Elena; Correa-Pérez, Andrea (The Cochrane database of systematic reviews, 2024)
BACKGROUND: Atherosclerotic cardiovascular disease (ACVD) is worsened by chronic inflammatory diseases. Interleukin receptor antagonists (IL-RAs) and tumour necrosis factor-alpha (TNF) inhibitors have been studied to see if they can prevent cardiovascular events. OBJECTIVES: The purpose of this study was to assess the clinical benefits and harms of IL-RAs and TNF inhibitors in the primary and secondary prevention of ACVD. SEARCH METHODS: The Cochrane Heart Specialised Register, the Cochrane Central Register of Controlled Trials (CENTRAL), Ovid MEDLINE (including In-Process & Other Non-Indexed Citations), Ovid Embase, EBSCO CINAHL plus, and clinical trial registries for ongoing and unpublished studies were searched in February 2024. The reference lists of relevant studies, reviews, meta-analyses and health technology reports were searched to identify additional studies. No limitations on language, date of publication or study type were set. SELECTION CRITERIA: RCTs that recruited people with and without pre-existing ACVD, comparing IL-RAs or TNF inhibitors versus placebo or usual care, were selected. The primary outcomes considered were all-cause mortality, myocardial infarction, unstable angina, and adverse events. DATA COLLECTION AND ANALYSIS: Two or more review authors, working independently at each step, selected studies, extracted data, assessed the risk of bias and used GRADE to judge the certainty of evidence. MAIN RESULTS: We included 58 RCTs (22,053 participants; 21,308 analysed), comparing medication efficacy with placebo or usual care. Thirty-four trials focused on primary prevention and 24 on secondary prevention. The interventions included IL-1 RAs (anakinra, canakinumab), IL-6 RA (tocilizumab), TNF-inhibitors (etanercept, infliximab) compared with placebo or usual care. The certainty of evidence was low to very low due to biases and imprecision; all trials had a high risk of bias. Primary prevention: IL-1 RAs The evidence is very uncertain about the effects of the intervention on all-cause mortality(RR 0.33, 95% CI 0.01 to 7.58, 1 trial), myocardial infarction (RR 0.71, 95% CI 0.04 to 12.48, I2 = 39%, 2 trials), unstable angina (RR 0.24, 95% CI 0.03 to 2.11, I2 = 0%, 2 trials), stroke (RR 2.42, 95% CI 0.12 to 50.15; 1 trial), adverse events (RR 0.85, 95% CI 0.59 to 1.22, I2 = 54%, 3 trials), or infection (rate ratio 0.84, 95% 0.55 to 1.29, I2 = 0%, 4 trials). Evidence is very uncertain about whether anakinra and cankinumab may reduce heart failure (RR 0.21, 95% CI 0.05 to 0.94, I2 = 0%, 3 trials). Peripheral vascular disease (PVD) was not reported as an outcome. IL-6 RAs The evidence is very uncertain about the effects of the intervention on all-cause mortality (RR 0.68, 95% CI 0.12 to 3.74, I2 = 30%, 3 trials), myocardial infarction (RR 0.27, 95% CI 0.04 to1.68, I2 = 0%, 3 trials), heart failure (RR 1.02, 95% CI 0.11 to 9.63, I2 = 0%, 2 trials), PVD (RR 2.94, 95% CI 0.12 to 71.47, 1 trial), stroke (RR 0.34, 95% CI 0.01 to 8.14, 1 trial), or any infection (rate ratio 1.10, 95% CI: 0.88 to 1.37, I2 = 18%, 5 trials). Adverse events may increase (RR 1.13, 95% CI 1.04 to 1.23, I2 = 33%, 5 trials). No trial assessed unstable angina. TNF inhibitors The evidence is very uncertain about the effects of the intervention on all-cause mortality (RR 1.78, 95% CI 0.63 to 4.99, I2 = 10%, 3 trials), myocardial infarction (RR 2.61, 95% CI 0.11 to 62.26, 1 trial), stroke (RR 0.46, 95% CI 0.08 to 2.80, I2 = 0%; 3 trials), heart failure (RR 0.85, 95% CI 0.06 to 12.76, 1 trial). Adverse events may increase (RR 1.13, 95% CI 1.01 to 1.25, I2 = 51%, 13 trials). No trial assessed unstable angina or PVD. Secondary prevention: IL-1 RAs The evidence is very uncertain about the effects of the intervention on all-cause mortality (RR 0.94, 95% CI 0.84 to 1.06, I2 = 0%, 8 trials), unstable angina (RR 0.88, 95% CI 0.65 to 1.19, I2 = 0%, 3 trials), PVD (RR 0.85, 95% CI 0.19 to 3.73, I2 = 38%, 3 trials), stroke (RR 0.94, 95% CI 0.74 to 1.2, I2 = 0%; 7 trials), heart failure (RR 0.91, 95% 0.5 to 1.65, I2 = 0%; 7 trials), or adverse events (RR 0.92, 95% CI 0.78 to 1.09, I2 = 3%, 4 trials). There may be little to no difference between the groups in myocardial infarction (RR 0.88, 95% CI 0.0.75 to 1.04, I2 = 0%, 6 trials). IL6-RAs The evidence is very uncertain about the effects of the intervention on all-cause mortality (RR 1.09, 95% CI 0.61 to 1.96, I2 = 0%, 2 trials), myocardial infarction (RR 0.46, 95% CI 0.07 to 3.04, I2 = 45%, 3 trials), unstable angina (RR 0.33, 95% CI 0.01 to 8.02, 1 trial), stroke (RR 1.03, 95% CI 0.07 to 16.25, 1 trial), adverse events (RR 0.89, 95% CI 0.76 to 1.05, I2 = 0%, 2 trials), or any infection (rate ratio 0.66, 95% CI 0.32 to 1.36, I2 = 0%, 4 trials). No trial assessed PVD or heart failure. TNF inhibitors The evidence is very uncertain about the effect of the intervention on all-cause mortality (RR 1.16, 95% CI 0.69 to 1.95, I2 = 47%, 5 trials), heart failure (RR 0.92, 95% 0.75 to 1.14, I2 = 0%, 4 trials), or adverse events (RR 1.15, 95% CI 0.84 to 1.56, I2 = 32%, 2 trials). No trial assessed myocardial infarction, unstable angina, PVD or stroke. Adverse events may be underestimated and benefits inflated due to inadequate reporting. AUTHORS' CONCLUSIONS: This Cochrane review assessed the benefits and harms of using interleukin-receptor antagonists and tumour necrosis factor inhibitors for primary and secondary prevention of atherosclerotic diseases compared with placebo or usual care. However, the evidence for the predetermined outcomes was deemed low or very low certainty, so there is still a need to determine whether these interventions provide clinical benefits or cause harm from this perspective. In summary, the different biases and imprecision in the included studies limit their external validity and represent a limitation to determining the effectiveness of the intervention for both primary and secondary prevention of ACVD.
Keywords: Receptors, Interleukin-1; Humans; Antibodies, Monoclonal, Humanized; Cause of Death; lidé; TNF-alfa; Angina, Unstable; ateroskleróza; Atherosclerosis; Myocardial Infarction; Randomized Controlled Trials as Topic; Bias; zkreslení výsledků (epidemiologie); randomizované kontrolované studie jako téma; primární prevence; nestabilní angina pectoris; Secondary Prevention; sekundární prevence; humanizované monoklonální protilátky; receptory interleukinu-1; Primary Prevention; Tumor Necrosis Factor-alpha; infarkt myokardu; příčina smrti